O corpo feminino na escultura dos anos 50 em Portugal : escultores formados pela ESBAL - Dias, Aida Costa de Sousa (2014)
In the beginning of the XX century, the Portuguese sculpture still mirrored the rules established by the neo-classicism and the naturalism. Nevertheless, Rodin Bourdelle and Francisco Franco were already recognized, by the portuguese sculptures, as leading references in sculpture renewal and respective conservative concepts. After the Portuguese World Exposition, the majority of sculpture limit they’re artistic work to government orders, whom discovers in the sculptures a complement to public infrastructures and simultaneously a way of celebration of heroes and myths. To the limited sculptures to the iconographic patterned sculpture, remains little time to the renovation of the forms and shapes, and ideas. The inspiration remains unknown, but the transpiration is known (Leopoldo would comment). With the conviction that a Sculpture can translate other concepts, we tried to find through the womam figure representation in the sculpture of the 50’s, how it was reproduced and what reasons led the sculptures to use the feminine body as a model, and at the same time try to know better our sculpture, wich is almost unstudied